El pensamiento formal y su influencia en el proceso de aprendizaje de niños y niñas de séptimo año de educación general básica, paralelos a y b, del centro educativo “Patria”, de la parroquia Cebadas, cantón Guamote, provincia de Chimborazo, durante el periodo escolar 2011-2012. - Bautista Guerrero, María Violeta (2012)
The present work has the purpose of analyzing, to describe and to qualify the development of the Formal Thought and its influence in the process of children's learning and seventh year-old girls, parallel TO and B, of the Educational Center "Homeland", of the fed parish, canton Guamote, county of Chimborazo, during the school period 2011-2012. He/she was carried out with the desire of to improve and to transform the reality socio educative, so that the children and girls acquire the dexterities cognitive, affective and psychomotor, to face with success the demands of the new learning concept, to solve problems of the life and to act positively in the society. To achieve these purposes it was carried out a qualitative investigation, of field and action in their descriptive and explanatory levels that it is based on based methodological courts, in the social interaction using methods of gathering of data that are not quantitative, with the purpose of to explore the social relationships and to describe the reality just as they experience it the corresponding ones; which were developed in four moments with their respective constituent elements: The Problem; Theoretical Marco; Methodology and the Marco Office worker. In the first stage he/she was carried out an analysis of the community context, by means of shops of which several problems were extracted, same that were analyzed in way participative and reflexive, it stops then to prioritize the problem reason of our investigation. A bibliographical revision of current authors was made on the topic that was good us to endorse the work. We also present with clarity the point of view according to our experience, same that made possible to sustain the investigative work. In the Theoretical Marco we assume the theoretical budgets, concepts, and other elements. The position of an investigation cannot be carried out if it doesn't become explicit that that we intend to know: it is always necessary to distinguish among what is known and what is not known with regard to a topic to define the problem that he/she will investigate clearly. The correct position of an xvi investigation problem allows to be defined its general and specific objectives, as well as the delimitation of the study object. The conceptual definition is necessary to unite the study to the theory and the operational definitions are essential to be able to carry out any investigation, since the data should be picked up in terms of having made observables This derived scientific conception, it was good us to emit the hypothesis appropriately with their respective variables, for a clear, coherent and practical study that improves the formal thought of children and girls. The methodology explains the applied pattern, the population or elected universe neatly according to the topic, making an exhibition of the selected instruments and its operative procedure. In the gathering of data the Technique of the Survey was used applied to educational, family parents and children and girls and the interview to the corresponding authority. This allowed us to pick up the information that left it systematizing in order to carry out the respective analysis and interpretation of results parallel way. The analysis and discussion of results are exposed through squares, graphics and their corresponding interpretations, conclusions and recommendations, as well as the confirmation of the hypothesis with the help of the descriptive statistic supported in the percentage method; this non alone investigation seeks to arrive until the part of the conclusions and recommendations, but the one of formulating a proposal, after the analysis made on the base of the results obtained in global form that can be presented as methodological strategies to develop the formal thought of children and girls of seventh year of Basic General Education of the Native school of the Fed parish, canton Guamote, county of Chimborazo" It is an important proposal to propitiate procedures that exercise a methodological process; that he/she favors to learn contents, to develop dexterities and abilities, based on the conformation of cooperative groups; to lay the foundation work habits gradually in the students, a positive attitude in front of themselves, not of repetition, reception or uniformity, but on the contrary, a search attitude, of xvii interrogation, of doubt, of interpretation, of opinion and of creation of valuable elements for a significant learning and constructivista in function of the context and the particular situations that it faces in their educational activity the boy (to) and the teacher like professional of the education